Hasil Belajar Teks Eksplanasi Menggunakan Media Audio Visual Youtube pada Siswa kelas XI di MA Sumber Bungur - Febrianty, Novita; Susanti, Aria Indah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Apart from providing entertainment, YouTube media can also be used as a source of knowledge in the field of education. Explanatory text is text that describes the occurrence of a phenomenon so that readers can clearly understand the background of the phenomenon. The aim of this research is to describe the results of learning explanatory texts using YouTube audio-visual media for class XI students at MA Sumber Bungur, Pamekasan. This research is a quantitative type with a quasi-experimental research design using a pre-test post-test control group. The data source is students of class XI IPA 1 and XI IPA 2 MA Sumber Bungur. The sample used in this research used a purportive sampling technique. Data collection techniques used tests and non-tests with expert tests on cognitive, affective and psychomotor aspects. In testing the hypothesis, the researcher used the Independent Sample T-test. The results of this research show that comparing the results of the hypothesis in the post-test with data analysis of learning results from explanatory texts, namely data processing using hypothesis testing (t test) with SPSS 26 produces a value (sig.2 - tailed) at a significance level of 5% (0.05). The learning results of the hypothesis test (t test) show that Ha is accepted and H0 is rejected. Students who use YouTube learning materials on average have better learning outcomes than students who do not use YouTube learning materials. The percentage gain is 96%.